The performance analysis of SEMA system - LI Li-chun; RAN Chong-sen; FAN Shao-jie; WEI Feng (Tongxin xuebao)
A novel kind of spread spectrum system is introduced. The enhanced transmission security arises from the special spectrum spreading and de-spreading processes. By statistical analyzing, the characters of the MAI and self-interference are studied and the numerical results of the error bit rate are given.